Joel Scott, translator. The Aesthetics of Resistance, Volume II. By Peter Weiss. Duke UP, 2020. - Mona Eikel-Pohen (Studies in 20th & 21st Century Literature, 2022)
Review of Joel Scott, translator. The Aesthetics of Resistance, Volume II. By Peter Weiss. Duke UP, 2020. x + 320pp.
Keywords: Peter Weiss; Aesthetics of Resistance; translation; Joel Scott